Ergonomic Risk Assessment for Musculoskeletal Disorders among Ultrasonologists of Peshawar: A Cross- Sectional Survey - Zia, Huma; Rehman, Muheebur; Khan, Sitara Hayat; Aman, Saba; Tahreem, Shumaila (Darul Yasin Al Sys, 2023)
Background: Ergonomics is the study of analyzing the demands of a task and aligning them with the abilities of the worker to establish an optimal work environment that minimizes the likelihood of injuries while maximizing efficiency. In safety and ergonomic literature, risk factors and consequent risks are common conceptions. Ergonomics has an impact on the adapted posture of workers developed due to the demand of their work procedure. Disorders related to bad posture and usage of different equipment and tools in a workplace can be solved through better ergonomics. Objective: To determine the ergonomic risk assessment for musculoskeletal disorders among Ultrasonologists of Peshawar. Methods: A cross-sectional study was conducted on a total of 117 participants from both public and private sector hospitals of Peshawar. Census sampling technique was used to select the participants. Consent was obtained and data was recorded using the Rapid Upper Limb Assessment (RULA) questionnaire. Results: Among the participants (n=117), majority were from the age group 31-40 years, n=48 (41%) with a mean age of 36 ± 7. Regarding the gender distribution, males were greater in number, n=88 (75.2%). The ergonomic risk for musculoskeletal disorders reveals that, majority of the participants fall in the medium risk, followed by low risk, negligible risk and very high risk, respectively. The analysis showed statistically significant association of ergonomics risk with age, gender, working hours, organization and work experience. Conclusions: It was concluded that the ergonomic risk for musculoskeletal disorders among Ultrasonologists is moderate to low followed by high risk. Males have higher ergonomic risk compared to females. Further investigations are needed.